The initial experience and response of vascular surgeons in Michigan during the COVID-19 pandemic. (December 2021) - Mouawad, Nicolas J; Lin, Judith C; Coleman, Dawn M; Simmons, Justin; Kabbani, Loay S; Cuff, Robert F; Mansour, M Ashraf
Background/Objective: The unprecedented pandemic spread of the novel coronavirus has severely impacted the delivery of healthcare services in the United States and around the world, and has exposed a variety of inefficiencies in healthcare infrastructure. Some states have been disproportionately affected such as New York and Michigan. In fact, Detroit and its surrounding areas have been named as the initial Midwest epicenter where over 106, 000 cases have been confirmed in April 2020. Method, Results and Conclusions: Facilities in Southeast Michigan have served as the frontline of the pandemic in the Midwest and in order to cope with the surge, rapid, and in some cases, complete restructuring of care was mandatory to effect change and attempt to deal with the emerging crisis. We describe the initial experience and response of 4 large vascular surgery health systems in Michigan to COVID-19.